Investment Strategies for Northern Cash Windfalls: Learning from the Alaskan Experience - Robinson, Michael; Pretes, Michael; Wuttunee, Wanda (ARCTIC, 1989)
The Alaska Native Claims Settlement Act (1971) and the creation of the Alaska Permanent Fund (1976) provided Native and non-Native Alaskans with two means of trust capital investment. To date Native Alaskans have largely chosen a strategy of investment in local established and/or new businesses, while the Permanent Fund has pursued a portfolio management strategy. Both investment means were examined against their stated ends (for the former: profit, social responsibility and cultural preservation; for the latter: savings, profit, and dividend distribution). It is concluded that business risk investment in an isolated and remote northern state characterized by economic reliance on externally controlled business cycles is inherently risky and that a strategy of international portfolio management has paid far superior dividends. Given that the current situation in the Canadian North (two Northern Accord agreements-in-principle and the Dene/Metis and Yukon Comprehensive Land Claim agreements-in-principle achieved in 1988) parallels the situation in Alaska in the 1970s, the authors propose a strategy for the creation of a model developmental natural resource trust fund based on the best features of the Alaskan models. This model fund combines a portfolio management trust philosophy with the goal of sustainable economic development in the quest for northern fiscal autonomy.Key words: Alaska Native Claims Settlement Act, Alaska Permanent Fund, resource management, Native people, economic development, sustainable development, trust funds, investment, Native land claims Mots clés: Alaska Native Claims Settlement Act, Alaska Permanent Fund, gestion de ressources, autochtones, développement économique développement durable, fonds de placement, investissement, revendications territoriales des autochtones